Hereditary neuropathy with liability to pressure palsies presenting with sciatic neuropathy. (17th October 2014) - Topakian, Raffi; Wimmer, Sibylle; Pischinger, Barbara; Pichler, Robert
Abstract : Hereditary neuropathy with liability to pressure palsies (HNPP) is an autosomal-dominant disorder associated with recurrent mononeuropathies following compression or trivial trauma. Reports on sciatic neuropathy as the presenting manifestation of HNPP are very scarce. We report on a 21-year-old previously healthy man who was admitted with sensorimotor deficits in his left leg. He had no history of preceding transient episodes of weakness or sensory loss. Clinical and electrophysiological examinations were consistent with sciatic neuropathy. Cerebrospinal fluid investigation and MRI of the nerve roots, plexus, and sciatic nerve did not indicate the underlying aetiology. When extended electrophysiological tests revealed multiple subclinical compression neuropathies in the upper limbs, HNPP was contemplated and eventually confirmed by genetic testing.